Content of vol. 27, 2024, Journal Scientific and Applied Research: Content of vol. 27, 2024, Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
Content of vol. 27, 2024, Journal Scientific and Applied Research